Automated Rest API generator based on Spring Framework and Beetl template engine - Chavez Chavez, Alvaro (2022)
API REST is currently the most widely used application development approach worldwide, however, a large percentage of development is repetitive. Repetition in development generates waste of time and money. For this purpose, EasyRest is proposed, a project for automatic generation of API Rest based on Spring Framework. For the development of this proposal, a custom archetype was built in Apache Maven. In addition, the construction of templates based on Beetl is performed. The proposal generates a Rest backend project, which contains controllers, services and repositories. The results obtained with the proposal were able to significantly reduce the time required for the construction of API Rest, compared to a manual construction. As a conclusion, the EasyRest proposal allows the automatic creation of API's Rest in a minimum of development time, automating the development of backend projects.